39.7k views
2 votes
Simplify and expand (X+3)(x-3)(3x+3)


User Pallav Raj
by
4.1k points

2 Answers

1 vote

Answer: 3x^3 + 3x^2 - 27x - 27

===============================================

Work Shown:

(x+3)(x-3)(3x+3)

(x^2-9)(3x+3) .... difference of squares rule

y(3x+3) .... let y = x^2-9

y*3x + y*3 .... distribute

3x( y ) + 3( y )

3x( x^2 - 9 ) + 3(x^2 - 9) .... plug in y = x^2-9

3x*x^2 + 3x*(-9) + 3*x^2 + 3*(-9) .... distribute

3x^3 - 27x + 3x^2 - 27

3x^3 + 3x^2 - 27x - 27

User Otto Allmendinger
by
4.7k points
2 votes

Answer:

3x^3 + 3x^2 - 27x - 27

Explanation:

User Adel Ben Hamadi
by
4.5k points